Cultural aspects of sustainable development - Małgorzata Pink (Economic and Environmental Studies (E&ES), 2018)
The main objective of this paper is to identify cultural aspects of sustainable development, by examining the interdependence of selected cultural characteristics and the index of sustainable development. Accordingly, the hypothesis of this article is that: Sustainable development achieves higher rates in countries that have a specific cultural profile, representing the values of western civilisation. The hypothesis was verified using Pearson's interdependence test. The arguments adopted in the tests described cultural features such as the distance to power, masculinity vs. femininity, individualism vs. collectivism, a degree of avoidance of uncertainty, long term orientation, indulgence and also materialism and postmaterialism syndromes in the context of the SDG index. Due to the specific nature of the data, the number of observations in individual tests ranges from 19 to 94. Data describing materialism and post-materialism are related to the period 2010-2014. other cultural data come from permanent indexes developed and made available within the Hofstede Insight project, Index SDG is given for 2016. The hypothesis has been verified. There is a positive correlation between values defining European culture and the SDG index. The conclusions resulting from this observation were formulated regarding the specificity of sustainable development in the cultural context.
Keywords: A13; Q01; 330; sustainable development; factors; culture; civilization